Sexism in esports : How male and female players evaluate each others’ performance and agency - Trepanowski, Radosław; Laato, Samuli; Drążkowski, Dariusz; Hamari, Juho; Kopeć, Zuzanna (Pergamon Press, 2025)
While equality and inclusivity are promoted in the realm of esports, most gamer communities remain male-dominated, which may give rise to prejudices against female players and their skill. In this study, we conducted two experiments where we measured how participants evaluate players’ performance and agency attributions. Using two distinct experimental manipulations—one utilizing videos of players playing (n = 312) and the other using narrative vignettes (n = 338)—we found that males are rated mostly based on their gaming outcomes, while females are more often judged based on pre-existing (prejudiced) preconceptions. These results contribute to the literature on gaming-related stereotypes by enhancing the understanding of societal prejudices in the evaluation of players’ skills.